Estimate of future blood demand in Japan and the number of blood donations required. (14th September 2018) - Kano, Chiharu; Takanashi, Minoko; Suzuki, Asami; Kawahara, Kazuo; Chiba, Koichi; Nakanishi, Hideo; Takamatsu, Junki; Kitai, Akiko; Takahashi, Koki
Abstract : Background and Objectives: An ageing population is an important factor for future blood demand estimates, but there are other factors that will affect transfusion medicine. To meet the demand, donor population changes must be considered. Materials and Methods: A survey was conducted at 672 medical institutions across the country on the prospects of progress in medical technology, prospects in medical systems, patient populations, etc., and this was translated to blood product usage estimates for 2022 and 2027. Using our 2016 data for blood collection, processing and supply, we calculated the necessary number of blood donations to fulfil the future demand. Future donation rates were calculated using the rates of change from 2011 to 2016 for each age group. Results: Predicted demand for blood products in 2022 compared to 2016 showed slight increases of 1·6% for RBC and 3·0% for PC, but a 0·3% decrease in FFP. The 2027 demand compared to 2016 was predicted to decrease 1·3% for RBC, 0·2% for PC and 3·6% for FFP. The eligible donor populations for 2022 and 2027 were forecast at 2 741 574 (99·3% of 2016) and 2 677 711 (97·0%), respectively. The required donation numbers were calculated as 4 851 968 (100·5% of 2016) and 4 767 676 (98·7%) for 2022 and 2027. We need to increase the donation frequency per donor from 1·75 in 2016 to 1·77 in 2022 and 1·78 in 2027. Conclusion: Because of medical practice changes, the demand‐donation discrepancy was not large for 2022 and 2027. We need to continue evaluating our practices and blood usage.